Analysis on the effect of wing geometry on underwater glider hydrodynamics - Eh Chu, Eentri (2017)
Unmanned Underwater Vehicle (UUV) has proven very useful in applications including defense system,seabed pipeline inspection, surveillance and exploration. Fin system in Unmanned Underwater Vehicle (UUV) is one of the important components in UUV which will guide the navigation and influence the trajectory flow of UUV. However, current research conducted on the feasibility and possibility using flexible wing system in UUV is limited.The objective of this project is to propose few design concept wing system in UUV, to analyze and select a suitable design concept for the wing system by using Analytical Hierarchy Process (AHP) and evaluate the feasibility of the proposed design concept in Underwater Glider by SolidWorks simulation. Nowadays,adaptive and morphing structures in complex aerospace vehicle have experienced a huge research due to their ability to optimize the stability of spacecraft's navigation control. Such adaptive and morphing structures have been investigated heavily and put to use extensively in the spacecraft industry.However, there are some considerations and limitations on the design of flexible wing system due to the wing geometry and unknown hydrodynamics in underwater. One of the considerations is how to define which designs of flexible wing system is the most suitable in UUV.In this study, AHP method was used to investigate the most suitable design of flexible wing system of UUV. SolidWorks simulation was used to demonstrate the effect of wing geometry in terms of buoyancy force, UUV's speed,endurance of proposed flexible wing system and underwater hydrodynamic flow trajectory. The simulated results clearly demonstrate the feasibility of proposed flexible wing system in Underwater Glider.